Sonochemical synthesis and characterization of biocl nanoplates and their photodegradation of rhodamine b - P. Intaphong (2020)
© S.C. Virtual Company of Phisics S.R.L. All rights reserved. BiOCl nanoplates were successfully synthesized by a simple sonochemical method at the pH of 2–12. The effect of pH of precursor on phase, morphologies and photocatalytic reaction of BiOCl was investigated in this research. X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed the presence of pure tetragonal BiOCl phase with different morphologies (nanoplates, mesoporous hierarchical flowers of nanoplate petals and flowers-nanoplates mixture). The photocatalytic activities of the BiOCl nanoplates were evaluated through the degradation of rhodamine B (RhB) under visible-light irradiation. They were found that mesoporous hierarchical BiOCl flowers synthesized at the pH of 6 showed the highest photodegradation efficiency of 96.24 % within 20 min.